Measurement of the Ξ0 → Λγ decay asymmetry and branching fraction - Lai, A; Marras, D; Bevan, A; Dosanjh, R; Gershon, T; Hay, B; Kalmus, G; Lazzeroni, C; Munday, D; Olaiya, E; Parker, M; White, T; et al. (2004)
In data taken with the NA48 experiment at the CERN SPS in 1999, 730 candidates of the weak radiative hyperon decay Ξ0→Λγ have been found with an estimated background of 58±8 events. From these events the Ξ0→Λγ decay asymmetry has been determined to α(Ξ0→Λγ)=-0.78±0.18stat±0.06 syst, which is the first evidence of a decay asymmetry in Ξ 0→Λγ. The branching fraction of the decay has been measured to be Br(Ξ0→Λγ)=(1.16±0.05 stat±0.06syst)×10-3. © 2004 Elsevier B.V. All rights reserved.